1995
DOI: 10.1172/jci118143
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell injury initiates glomerular sclerosis in the rat remnant kidney.

Abstract: The development of progressive glomerulosclerosis in the renal ablation model has been ascribed to a number of humoral and hemodynamic events, including the peptide growth factor, transforming growth factor-j31 (TGF-fi1).An important role has also been attributed to angiotensin II (All), which, in addition to its hemodynamic effects, can stimulate transcription of TGF-fi1. We postulated that increased glomerular production of All, resulting from enhanced intrinsic angiotensinogen expression, stimulates local T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
118
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(127 citation statements)
references
References 47 publications
8
118
0
1
Order By: Relevance
“…It has been suggested that ANG II induces glomerular injuries through renal hemodynamic effects and stimulation of growth and extracellular matrix production by glomerular cells (30). Several studies on this subject have been published (4,(31)(32)(33), and several factors such as TGF-␤ and endothelin-1 have been identified as crucial components in the mechanism, but the detailed signaling mechanism responsible for the effects are largely unknown. PI3K, in the mesangial context, has been reported to induce proliferation (34), enhance collagen expression (24), and prevent apoptosis (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that ANG II induces glomerular injuries through renal hemodynamic effects and stimulation of growth and extracellular matrix production by glomerular cells (30). Several studies on this subject have been published (4,(31)(32)(33), and several factors such as TGF-␤ and endothelin-1 have been identified as crucial components in the mechanism, but the detailed signaling mechanism responsible for the effects are largely unknown. PI3K, in the mesangial context, has been reported to induce proliferation (34), enhance collagen expression (24), and prevent apoptosis (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 The primary action of the RAS is to regulate vascular tone and renal salt excretion. However, recent data indicate that, independently of its effects on blood pressure, AII may augment the accumulation of extracellular matrix.…”
mentioning
confidence: 99%
“…Endothelial injury is also involved in the initiation and propagation of glomerulosclerosis and ESRD (5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%